Evaluation of assistance systems allowing older drivers to intercept moving inter-vehicular space - Tran Van, Lola; Berthelon, Catherine; Navarro, Jordan; Goulon, Cédric; Mascret, Nicolas; Montagne, Gilles (Frontiers in Psychology, 2023)
The objective of the present study was to test two Advanced Driving Assistance Systems (ADAS) designed to help older drivers to intercept a moving inter-vehicular space. Older and younger drivers were asked to intercept a moving inter-vehicular space within a train of vehicles in a driving simulator. Three ADAS conditions (No-ADAS, Head Down, Head Up) as well as five distinct speed regulation conditions were tested. Vehicle trajectory, gaze behavior and acceptance were analyzed. Our results reveal that the ADAS tested make it possible to perform the interception task but also to reduce the variability of the behavior produced. They also indicate that the location of the augmented information provided by the ADAS directly impacts the information-gathering strategy implemented. Finally, whereas younger divers reported mixed levels of ADAS acceptance, older drivers reported a good level of acceptance. All these results could be particularly useful with a view of designing ADAS for older drivers.